GENERALIZED LIGAMENT LAXITY AND HIP ARTHROSCOPY IN AN ATHLETIC POPULATION. Issue 17 (24th October 2013) - Akhtar, MA; Campton, L
Abstract : This study was performed to assess the incidence of generalized ligament laxity (GLL) in patients undergoing hip arthroscopy for intraarticular hip pathology diagnosed by clinical examination and confirmed with magnetic resonance arthrography. Prospective data were collected for 27 patients between Feb and May 2013 under the care of a specialist hip surgeon including demographic details; mechanism of injury, operative diagnosis, surgical treatments performed and GLL by using the Beighton score. The mean age was 32 years (range 18–56). There were 14 male (52%) and 13 (48%) female patients. 81% patients were involved in sports and football was the most common sports in 55%. The mean duration of symptoms was 4 years (range 1–16). The mean Non-arthritic hip score was 30 (range 20–46). 80% patients denied hip injury, 8% had significant hip injury, 8% were involved in road traffic accidents and 4% had a trivial injury. 21% patients had bilateral, 67% had right and 12% had left sided symptoms. 54% patients had Femoroacetabular Impingement (FAI) and an associated labral tear, 31% had an isolated labral tear and 15% had only impingement. 42% patients had labral debridement and osteochondroplasty of the femoral neck, 19% had labral debridement, 15% had osteochondroplasty, 15% had labral repair and osteochondroplasty and 8% had only labral repair. The mean Beighton score for these patients was 2.7 (range 0–9). 10 patients (37%) in this group had a Beighton score of 4 or more indicating GLL. We found that there was a high incidence (37%) of GLL in patients undergoing hip arthroscopy. 54% patients had FAI and associated labral tear, 80% denied hip injury and 21% had bilateral symptoms. Further research to study the effect of GLL on intraarticular hip pathology in young athletic population is required for appropriate advice about the risk of injuries.